Image (Pre-image) Homomorfisme Interior Subgrup Fuzzy - Saman Abdurrahman (Program Studi Matematika Fakultas Sains dan Teknologi UIN Sunan Kalijaga Yogyakarta, 2019)
Dalam makalah ini, akan diperkenalkan notasi image (pre-image) di bawah homomorfisma grup, dan akan dibuktikan image (pre-image) interior subgrup fuzzy (interior subgrup) di bawah homomorfisma grup selalu interior subgrup fuzzy (interior subgrup). [In this paper, we will introduce the image (pre-image) under the group homomorphism, and we will prove the image (pre-image) of the interior of the fuzzy subgroup (the interior of the subgroup) under the group homomorphism is always the interior of the fuzzy subgroup (the interior of the subgroup).]